Profit Sharing Akad of Sharia Venture Capital Companies - Komarudin, Parman; Sodiki, Muhammad; Yanova, Muhammad Hendri; Hadi, Hendra; Yusuf, Mahmud (Fakultas Syariah INSURI Ponorogo, 2023)
This study aims to analyze the essence of profit sharing contracts for Islamic venture capital companies. This study uses a qualitative method which is a method that focuses on in-depth observation. Therefore, the use of qualitative methods in this study resulted in a more comprehensive review of profit-sharing contracts for Islamic venture capital companies. the type of research that the author uses is normative legal research. The nature of research in this writing is the nature of descriptive research. The approach used in this legal research is a statutory approach and a conceptual approach. The results of this study indicate that Islamic venture capital uses musyarakah and mudharabah akad in the profit-sharing scheme. Akad Musyarakah are used for companies that already have an ongoing business, but still need additional capital for business expansion purposes and akad mudharabah are used when a new business is established that has prospects for development.